Discontinuous laser dispersing of titanium nitride based hard ceramic particles for improving the tribological behavior of hot stamping tools - Schirdewahn, Stephan; Carstensen, Niels; Spranger, Felix; Hilgenberg, Kai; Merklein, Marion (Hot Sheet Metal Forming of High-Performance Steel, 2022)
Over the last decades, the application of ultra-high strength steel (UHSS) has constantly increased within the automotive industry due to its favorable strength-to-weight ratio. For manufacturing such steel grades to complex-shaped body-in-white parts, temperature-assisted forming operations are required. In this regard, hot stamping has been established as a suitable technology to generate geometrical complex car body components with high shape accuracy. During the forming operation, however, high thermo-mechanically tool stresses appear, which in turn promote the occurrence of severe wear and high friction values at the blank-die interface. Within short production periods, the quality of the parts as well as the operating time of the tool are negatively affected. For this purpose, an innovative surface engineering technology named laser implantation has been applied, in order to improve the tribological performance of hot stamping tools. The implantation technique is based on manufacturing highly wear-resistant, separated and elevated microfeatures onto the tool surface by embedding hard ceramic particles via pulsed laser radiation. To qualify the resulting tribological behavior, modified pin-on-disk tests have been performed under hot stamping conditions. Afterwards, optical and tactile measurements of the blank surface as well as Energy-dispersive X-ray spectroscopy (EDS) analysis on the worn tool topography have been carried out to clarify the cause-effect relations. The results have been compared to unmodified tooling systems, in order to evaluate the tribological impact of the laser implantation process. <